The Origin of Fast Lithium‐Ion Transport in the Inorganic Solid Electrolyte Interphase on Lithium Metal Anodes. Issue 8 (31st May 2022) - Ma, Xia-Xia; Shen, Xin; Chen, Xiang; Fu, Zhong-Heng; Yao, Nan; Zhang, Rui; Zhang, Qiang
Abstract : Solid electrolyte interphase (SEI) plays an indispensable role in stabilizing lithium metal batteries (LMBs). An ideal SEI is supposed to impede the electrolyte degradation on lithium metal anodes while allowing lithium‐ion transport. However, the ionic transport mechanism in SEI is not fully understood. Herein, first‐principles calculations are performed to probe the ionic transport mechanism in inorganic SEI and the role of carrier concentration is highlighted. The low ionic conductivity in bulk inorganic SEI (Li2 O, LiOH, Li2 CO3, and LiF) is ascribed to its low carrier concentration. The Li2 O/LiF interface delivers both a high carrier concentration and ionic conductivity despite an indifferent diffusion barrier. Herein, not only the lithium‐ion transport mechanism in inorganic SEI is unveiled but also the general references for the rational design of high‐ionic‐conductivity SEI on working Li‐metal anodes are afforded. Abstract : Herein, the lithium‐ion transport mechanism in inorganic solid‐state interphase (SEI) is comprehensively investigated through first‐principles calculations. The high ionic conductivity along with the interface between inorganic SEI compounds, which is even comparable to that of routine solid‐state electrolytes, is ascribed to the very high carrier concentration.